Sudan : Staff Report for the 2014 Article IV Consultation and Second Review Under the Staff-Monitored Program. (IMF Staff Country Reports; Country Report, 2014)
KEY ISSUES Context: Sudan's economy has yet to recover from the shock of South Sudan's secession three years ago, which took away three-quarters of oil production, half of its fiscal revenues, and two-thirds of its international payments capacity. Despite progress in implementing policies to address the resulting imbalances, inflation remains high and growth sluggish. Macroeconomic adjustment has been complicated by structural weaknesses, a heavy debt burden, U.S. sanctions, and volatile domestic and regional political factors. The authorities embarked earlier this year on a stabilization program supported by a Staff-Monitored Program (SMP). The program runs through end-2014, and the authorities have not yet decided if they want a new SMP; the mission for the third SMP review in December will discuss the matter with them. Developments, outlook, and risks. Economic performance this year has been mixed as growth has remained subdued and inflation still high at about 40 percent. Growth is expected to rebound in 2015, but the outlook remains uncertain. The risks are largely tilted to the downside, although prospects of a successful national dialogue could lead to resolution of domestic conflicts and improved international relations. Article IV. Discussions focused on policies to secure macroeconomic stability, strengthen social safety nets, and a move to sustainable and inclusive growth. Fiscal consolidation (through revenue mobilization and expenditure rationalization, including a gradual phase-out of fuel subsidies) should continue, accompanied by increased public investment and social spending. Tight monetary policy and lower central bank financing of the government should help lower inflation. There is also a need for steps to lower the large premium in the foreign exchange market. Stronger supervision is needed to improve banks' resilience. More should be done to improve the business climate to boost growth. Program performance: The program remains on track. The authorities continue to minimize non-concessional borrowing and maintain satisfactory track record of payments to the Fund. They recently devalued the official exchange rate by 3 percent to help address external imbalances, which together with a large appreciation of the parallel market rate, has helped lower the premium. Going forward, priority should be given to further reducing inflation by continuing fiscal consolidation, tightening monetary policy, and gradually closing the gap between the official and parallel exchange rates. Debt relief. Relief requires reaching out to creditors, normalizing relations with international financial institutions, and continuing to establish a track record of cooperation with the IMF on policies and payments. The authorities' agreement with South Sudan to extend the 'zero option' by two years is a positive step.